2016
DOI: 10.1016/j.neuropharm.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5-HT 3 receptors in the action of vortioxetine in rat brain: Focus on glutamatergic and GABAergic neurotransmission

Abstract: The antidepressant vortioxetine is a 5-HT3-R, 5-HT7-R and 5-HT1D-R antagonist, 5-HT1B-R partial agonist, 5-HT1A-R agonist, and serotonin (5-HT) transporter (SERT) inhibitor. Vortioxetine occupies all targets at high therapeutic doses and only SERT and 5-HT3-R at low doses. Vortioxetine increases extracellular monoamine concentrations in rat forebrain more than selective serotonin reuptake inhibitors (SSRI) and shows pro-cognitive activity in preclinical models. Given its high affinity for 5-HT3-R (Ki = 3.7 nM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 49 publications
2
81
0
1
Order By: Relevance
“…Vortioxetine is a 5-HT transporter protein (SERT) inhibitor, a 5-HT 1A receptor agonist, 5-HT 1B receptor partial agonist, and 5-HT 1D , 5-HT 3 , and 5-HT 7 receptor antagonist (Sanchez et al, 2015). Interestingly, vortioxetine’s 5-HT receptor activity may confer the ability to indirectly modulate signaling through several other neurotransmitter systems, including norepinephrine, dopamine (Pehrson et al, 2013), acetylcholine (ACh) and histamine (Mørk et al, 2013), γ-aminobutyric acid (Pehrson and Sanchez, 2015; Dale et al, 2016), and glutamate (Dale et al, 2014; Pehrson and Sanchez, 2014; Riga et al, 2016). Several of these neurotransmitter systems have known relationships to cognitive function, and we have hypothesized that vortioxetine’s cognitive effects may be specifically related to indirect modulation of γ-aminobutyric acid and glutamate neurotransmission (Pehrson and Sanchez, 2014), ACh, or histamine neurotransmission (Mørk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vortioxetine is a 5-HT transporter protein (SERT) inhibitor, a 5-HT 1A receptor agonist, 5-HT 1B receptor partial agonist, and 5-HT 1D , 5-HT 3 , and 5-HT 7 receptor antagonist (Sanchez et al, 2015). Interestingly, vortioxetine’s 5-HT receptor activity may confer the ability to indirectly modulate signaling through several other neurotransmitter systems, including norepinephrine, dopamine (Pehrson et al, 2013), acetylcholine (ACh) and histamine (Mørk et al, 2013), γ-aminobutyric acid (Pehrson and Sanchez, 2015; Dale et al, 2016), and glutamate (Dale et al, 2014; Pehrson and Sanchez, 2014; Riga et al, 2016). Several of these neurotransmitter systems have known relationships to cognitive function, and we have hypothesized that vortioxetine’s cognitive effects may be specifically related to indirect modulation of γ-aminobutyric acid and glutamate neurotransmission (Pehrson and Sanchez, 2014), ACh, or histamine neurotransmission (Mørk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vortioxetine is a 5‐HT 3 , 5‐HT 7 , and 5‐HT 1D receptor antagonist, 5‐HT 1B receptor partial agonist, and 5‐HT 1A receptor agonist, in addition to a 5‐HT transporter inhibitor . Nonclinical data suggest that vortioxetine modulates direct and indirect multiple neurotransmitters in the brain, including serotonin, norepinephrine, dopamine, histamine, acetylcholine, γ‐aminobutyric acid (GABA), and glutamate . Vortioxetine's multimodal mechanism of action implies a differentiated profile from conventional antidepressants .…”
mentioning
confidence: 99%
“…8,9 Nonclinical data suggest that vortioxetine modulates direct and indirect multiple neurotransmitters in the brain, including serotonin, norepinephrine, dopamine, histamine, acetylcholine, γ-aminobutyric acid (GABA), and glutamate. 8,[10][11][12] Vortioxetine's multimodal mechanism of action implies a differentiated profile from conventional antidepressants. 8 Phase 2 and 3 clinical trials conducted in the USA and Europe have demonstrated the antidepressant efficacy of vortioxetine in MDD patients at doses of up to 20 mg/day.…”
mentioning
confidence: 99%
“…Conversely, blockade of 5-HT3 receptors by vortioxetine reduces the GABAergic tone on GABAA and GABAB receptors, which then translates into a disinhibition of the activity of midbrainprojecting pyramidal neurons in the mPFC (Riga et al, 2016) (Fig. 4).…”
Section: Development Of Multi-target Antidepressantsmentioning
confidence: 99%
“…This prefrontalbrainstem connectivity may account for the rapid recovery of serotonergic activity after repeated vortioxetine treatment (Bétry et al, 2013). In addition, 5-HT3 receptor blockade potentiates the increase in extracellular 5-HT produced by SERT blockade, an effect likely involving the removal of a GABAB tone on 5-HT axon terminals (Riga et al, 2016). These effects may account for the greater enhancement of forebrain monoamine release produced by vortioxetine, as compared with SSRI (Mork et al, 2012).…”
Section: Development Of Multi-target Antidepressantsmentioning
confidence: 99%